Analysis of Takaful vs. conventional insurance firms' efficiency: Two-stage DEA of Saudi Arabia's insurance market - Tarifa Almulhim (Cogent Business & Management, 2019)
Despite the remarkable growth in the insurance industry over the past two decades, few studies evaluate the performance of Takaful vs. conventional insurance firms with focus on the standard structure of production as a two-stage process, that is, operations and profitability. Thus, this research examines the performance of Saudi Arabia's insurance market using a two-stage data envelopment analysis to assess the efficiency of the two production stages and accordingly, define the leader stage. The empirical results obtained using data for 26 conventional and seven Takaful insurance firms for 2014-2017 indicate declining average efficiency scores for both firm types. In other words, Saudi Arabia's insurance market warrants new consolidation and foreign participation regulations to assist firms in becoming dynamic and strong. This study makes a significant contribution given the dearth of an exclusive analysis on the two-stage efficiency of Saudi Arabia's Takaful and conventional insurance firms. Further, it offers key implications for decision makers, regulators, and managers associated with the insurance industry in Saudi Arabia and other emerging insurance markets.
Keywords: 650; Takaful firms; Saudi Arabian insurance market; two-stage data envelopment analysis; efficiency